Macroscopic characterization of injuries produced in fights with medical-legal implications. Mexico State, 2023 - Crhistian Adán Hurtado; Georgina Jiménez Estrada; Víctor René Navarro Machado (Medisur)
Foundation: personal injuries due to trauma have diverse etiologies and medical-legal implications. Objective: to macroscopically characterize the injuries produced in fights with medical-legal implications, in the State of Mexico. Methods: a descriptive, cross-sectional study, with a universe of cared users (aggressors and victims for this cause) who filed a complaint for injuries resulting from a fight, from January to November 2023 and who gave their consent. Information was obtained from interviews and clinical examinations conducted by the lead author in a doctor's office. For statistical analysis, absolute frequencies and percentages were used. Results: 52 patients were studied, of which 33 were women (63, 46%), single lesions predominated (21 cases: 40.38% mainly on the face) or in two areas (10 cases: 19.23%) of the body; the maximum was 11 different lesions in two patients. A total of 158 injuries were described, with a predominance of excoriations (54.43%) and ecchymoses (41.77%). 46.15% of the patients received injuries on both sides of the body, followed by those who presented them on the right side (30.77%); 51.27% of the lesions were located in this body. In 77 injuries (48.73%), the largest diameter measured between 2-4 centimeters. No transient or permanent functional disorders are described. Conclusions: the fight injuries, with medical-legal implications, had a forceful injury mechanism and were mainly superficial, single, small, in the upper part of the body and without functional sequelae.